Conceptual Analysis of a Terminological Unit in the Light of Modern Cognitive Terminology - Abdullina, Nazgul U.; Aydarbek, Karlygash Zh. (Opción)
The purpose of the study is to trace the relationship of the term as a linguistic unit and the concept as a unit of thinking through a conceptual analysis of terms. Since the main method of the cognitive approach is associated with determining the essence and nature of the considered term concepts, the conceptual analysis of terms comes to the fore. The result of the study showed that the term, being a certain layer of the lexicology of the language, is connected with the notion of the concept in such a way that the signs defining its definition are at the same time constituent components of the concept content, a kind of “filling” the frame slots - as the structure of the concept.